Method of calculating the amount of leakage of compressed air from the systems based on the analysis of transient processes - G. V. Gogrichiani (Вестник Научно-исследовательского института железнодорожного транспорта)
An important task for the industry, including railway transport, is the possible reduction of electricity costs. In this regard, attention is drawn to the work of the compressor units and stations, aimed not only at providing the consumer with compressed air, but also compensating for air mass leakage through leaks in networks and technological equipment. The article suggests an engineering method to determine the value of leakage in any technical complexes per unit of time and the possibility to estimate costs needed to eliminate this process which might be harmful to production. The essence of the proposed method is to analyze one element of automatic operation cycle of the compressor unit together with the pneumatic network when consumers are switched off, where the operating pressure is maintained within a predetermined range. This is defined by the mass of compressed air supplied to the pneumatic network from the compressor and spent on making-up for the leak, i.e. the quantities of compressed air which get through leakiness of the system.